硬口蓋に生じたglomus腫瘍の1例 - 堤, 泰彦; 弘部, 悠; 山本, 学; 町田, 好聡; 浅田, 泰幸; 家森, 正志 (日本口腔外科学会雑誌, 2019)
Glomus tumor is a benign tumor derived from glomus cells found in the arteriovenous anastomosis in the vascular plexus of the skin and nail bed. Typically, it is a reddish purple and painful tumor with a predilection site for arising in the extremities, especially the nail bed. There are a few reports of the tumor arising in the oral region as well. Here, we report a case of a glomus tumor that developed in the palate.　The patient was a 69-year-old woman who noticed a tumor in the left side of the palate around 2012, but left it untreated. In 2014, the mass gradually increased, and maladaptation of the denture occurred as a result of which she visited a local dentist. The patient was referred to our hospital for further examination.　An elastic soft mass approximately 20 mm in diameter was discovered in the hard palate in the left maxillary molar region. Biopsy results led to the diagnosis of a glomus tumor. In December 2014, the palatal tumor was resected with the patient under general anesthesia. Five years after operation, no recurrence tendency has been noted, and the postoperative course is favorable.